Comparison of biological and mechanical properties of different paranasal sinus mucosa in goat - Xinyu Fang; Cai Mi; Yingdi Wang; Yidan Sun; Jia Nie; Haoning Tang; Yajing Liu; Yanfeng Li; Jing Wang; Zheng Ma; Yishi Han (BMC, 2022)
Abstract Objective The present study was designed to explore endurable pressure intensity of different paranasal sinus mucosa in goats. Method Mucosa commonly involved in maxillary sinus augmentation, including mucosa from maxillary sinus crest, maxillary sinus floor, and frontal sinus, were harvested in a computed tomography-guided manner. The obtained mucosa was then sectioned into square and irregular ones for maximum endurable pressure intensity determination and morphological observation, respectively. Results Thickness of paranasal sinus mucosa, as determined under morphological staining by an optical microscope with a graduated eyepiece, were calculated. And the results showed that the average thickness of maxillary sinus crest mucosa, floor mucosa, and frontal sinus mucosa in goats were 410.03 ± 65.97 μm, 461.33 ± 91.37 μm and 216.90 ± 46.47 μm, respectively. Significant differences between maxillary sinus crest and frontal sinus, maxillary sinus floor, and frontal sinus were observed (P < 0.05). Maximum endurable pressure intensity was determined by utilizing a self-made clamp device and the results revealed maximum endurable pressure intensity of maxillary sinus crest mucosa, floor mucosa and frontal sinus mucosa in goats were 260.08 ± 80.12Kpa, 306.90 ± 94.37Kpa and 121.72 ± 31.72Kpa, respectively. Also, a statistically significant difference was observed when comparing the endurable pressure intensity between maxillary sinus crest and frontal sinus, maxillary sinus floor, and frontal sinus (P < 0.05). Further correlation analysis also revealed a positive correlation between the thickness of mucosa of the maxillary sinus and frontal sinus and maximum endurable pressure intensity (P < 0.05). Conclusion Mucosal thickness and maximum endurable pressure intensity of maxillary sinus crest and floor were larger than that of frontal sinus mucosa and a positive correlation between the thickness of mucosa and endurable pressure intensity was observed. Our results thus might provide an experimental basis and guidance for mucosa-related problems involved maxillary sinus augmentation.